Desain Karakter Webkomik Tentang Post-Traumatic Stress Disorder (PTSD) Untuk Usia 16-24 Tahun - Annisa Nugraini, Insan; Ismoyo Aji, Restu; Solicitor C. R. E Chidtian, Aileena (Besaung : Jurnal Seni Desain dan Budaya, 2025)
Post-Traumatic Stress Disorder (PTSD) is a mental health disorder that occurs after a person experiences or witnesses a traumatic event which can cause sufferers to experience excessive anxiety, flashbacks, nightmares and significant emotional disturbances. Based on this problem, the author is interested in raising the theme of designing PTSD in the context of adolescents aged 16-24 years. The main focus is depicting the main character's experiences and struggles in dealing with PTSD, as well as including messages of awareness and support for the target audience. This research uses qualitative methods and is supported by sources and data from interviews with experts, namely psychologists, official Webtoon comic artists, PTSD survivors themselves and is also strengthened by other supporting sources such as books or journals. Meanwhile, for the quantitative method, it is taken from the results of a questionnaire which shows the quantity for certain data collection needs. A problem-solving plan through comic character design that integrates artistic elements to support the narrative, including color, facial expressions, and body gestures, in creating emotional depth and reader engagement. It is hoped that the resulting comic will provide inspiration, support and enlightenment for individuals who may be experiencing PTSD or have friends and family who are affected. Thus, it is hoped that this design will be the first step in building public awareness of mental health problems among teenagers and early adults through media that is accessible and of interest to them.